A class of IIR filters synthesized using frequency-response masking technique - Liu, Qinglai (2022)
This letter presents a class of infinite impulse response (IIR) filters synthesized using a system of IIR subfilters based on the frequency-response masking (FRM) technique. In the proposed class of filters, the bandedge shaping filters are a parallel connection of two allpass filters, and the masking filters are approximately linear phase IIR filters composed of a parallel connection of a delay line and an allpass filter. A design method which jointly optimizes the IIR subfilters is introduced. The proposed class of IIR filters has lower coefficient sensitivity and roundoff noise compared with conventional IIR filters.